Computational study to understand mechanism of isoniazid drug resistance caused by mutation (R268H) in NADH dehydrogenase of Mycobacterium tuberculosis. (7th July 2019) - Jena, Lingaraja; Deshmukh, Shraddha; Nayak, Tapaswini; Wankhade, Gauri; Harinath, Bhaskar C.
NADH dehydrogenase (Ndh) of Mycobacterium tuberculosis is essential for conversion of NADH to NAD + in the presence of FMN. An increased NADH/NAD + ratio was reported due to mutation (R268H) in Ndh, causing INH resistance. To study the effect of this mutation on Ndh, molecular dynamics (MD) simulation analysis was performed for both wild and mutant models independently as well as for docked complexes (Ndh-NADH and Ndh-FMN). Simulation study showed that mutation (R268H) affected the secondary structure of the enzyme giving extra stability to the mutant model R268H as observed in the root mean square deviation (RMSD) plot. Furthermore, it was observed that both wild-type and mutant models of Ndh were quite stable in complex with NADH but in case of FMN, the Ndh mutant appears to be more unstable and might be the reason for decreasing NAD + concentrations thus hindering INH-NAD adduct formation resulting in isoniazid resistance.